Monster truck FERMIAC. Issue 4 (19th September 2018) - Urbatsch, Todd; Houdek, Connor
Abstract: After World War II, Los Alamos was anxious for its own computer. While on a walk along the river during a picnic with their families, Enrico Fermi outlined to L.D.P. King a plan for an analog computer to simulate neutron transport. L.D.P. King built it with materials lying around the Omega Site in Los Alamos Canyon. They used the "FERMIAC" for a couple of years, and it was forgotten, until 1966, when Bengt Carlson found it in his office. The lab drew up some blueprints and it went out on loan to the Smithsonian. It is now on display at LANL's Bradbury Science Museum. There still are several questions as to how the FERMIAC was used. The FERMIAC is too fragile to handle, so our plan in the summer of 2017 was to build a museum-quality replica, much like the Italians did last year. However, the summer student was leaving before it could be re-constructed. Thus, finding ourselves in a similar situation as Fermi and King, we developed our own one-speed neutron transporter fashioned out of the chassis of a toy monster truck. We describe our "Monster Truck FERMIAC" on an XY problem.